(untitled) (Księgarnia Akademicka Publishing, 2023)
BASICS OF TURKOLOGY FOR BALKANISTS Basics of Turkology for Balkanists offers a brief introduction to the little-known field of Rumelian studies, a discipline that concerns itself with the question of mutual influence between Turkish and the languages of the Balkans. At the same time, the author took advantage of this opportunity to present his own, hitherto unpublished views (see e.g. chapter 7). Besides the Introduction, the work consists of seven chapters: 1) Terms, classification, and the presence of Turkish in the Balkans; 2) The most important features of the Turkish language (presented in 25 thematic subchapters); 3) Turkish dialects of Anatolia and Rumelia; 4) The Karamanlides and the Karamanli dialect; 5) The Gagauz people and language; 6) Transcription texts and rhyming dictionaries; 7) Sample problems in Rumelian studies. The whole is completed by a Turkish-Polish glossary, bibliography, and a list of abbreviations. The aim of the book is to present problems in Rumelian studies in such a way as to enable the reader to independently navigate the specialist literature.